SOS: a silent threat. A case report on paracetamol overdose - Shreya Nagraj; Akshay Kumar N S; Manjari Sharma; Praveen Kumar (Emergency Care Journal)
Paracetamol, also known as acetaminophen, is a widely used non-opioid analgesic and antipyretic agent. As an easily accessible over-the-counter (OTC) medication, the risk of exceeding the maximum daily dosage and resulting in an overdose is significant. Here, we present a case of paracetamol overdose of a 24-year-old male who consumed 15 tablets (9.75 g) of paracetamol given as OTC to relieve his chest pain. The patient was treated with N-acetylcysteine (NAC) and managed symptomatically. This case involves a paracetamol overdose resulting from the patient’s inadequate comprehension of the term si opus sit (SOS), which translates to “as needed”. This case highlights the importance of patient counseling in the rational use of drugs.